Fake news on campus: Gauging the level of sharing among Malaysian university students - Wan Abu Bakar, Wan Hashridz Rizal; Ahmad, Abu Dzar; Mohd Azmi, Mohammad Haafiz Aminuddin; Ridzuan, Abdul Rauf; Hassan, Mohd Sufiean; Abdul Razak, Fahmi Zaidi (Journal of Islamic, Social, Economics and Development, 2025)
Text font is Times New Roman, 12 pt size, italic, and justify the alignment. This study investigates the prevalence of fake news sharing among Malaysian university students in light of the increasing reliance on social media as a primary information source. The spread of misinformation poses a significant challenge to public trust and media credibility, especially among digitally active youth. The research addresses the problem that many university students lack the critical skills needed to verify online content, making them vulnerable to both the consumption and dissemination of fake news. The primary objective was to assess the level of fake news sharing and identify patterns of behaviour related to information verification. A quantitative, cross-sectional research design was used, and data were collected through an online questionnaire distributed via Google Forms to 449 university students between January and February 2025. Using a five-point Likert scale, responses were analysed with IBM SPSS Statistics version 26. Findings revealed a high level of fake news sharing (M = 3.71, SD = 1.18), particularly among younger respondents aged 18 to 30, along with a significant reliance on social media and limited content verification practices. The study contributes to the growing discourse on digital media responsibility and emphasizes the urgency of implementing targeted media literacy programs within higher education institutions. Future research should consider broader demographic factors such as income and educational background and adopt qualitative or mixed-method approaches to explore underlying psychological and sociocultural influences.